The impact of perceived environmental uncertainty and individual differences on management information requirements: A research note - Fisher, Cathy (Accounting, Organizations and Society, 1996)
In this study it is hypothesised that as perceived environmental uncertainty (PEU) increases, internals on the Locus of Control (LOC) scale will perceive information that has wider scope and is timely to be more useful than do externals on the LOC scale. Results indicate a significant effect but in a direction opposite to that expected. Externals, not internals, found information more useful when faced with higher uncertainty. It is suggested that the source rather than the relevance of the information, as was predicted, may have contributed to this result. The study is significant because it supports the need to consider personality and environmental factors together.